2015
DOI: 10.3109/2000656x.2015.1062387
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the fast track surgery principles can reduce length of stay after autologous breast reconstruction using free flaps: A case control study

Abstract: By introducing a simple, peri- and postoperative care concept it is possible to reduce LOS after microsurgery by at least 1 day without an increase in complications or flap loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 20 publications
3
84
1
Order By: Relevance
“…Multiple meta‐analyses from colorectal and non‐colorectal abdominal surgeries all show faster recovery and in many operations also reduced complications. The same trend is true for many non‐abdominal surgeries, such as hip and knee replacement in the elderly, and plastic surgery . Large cohorts also indicate that introduction of ERAS programs may reduce the risks commonly associated with comorbidities such as diabetes .…”
Section: Gains From Implementation Of Erasmentioning
confidence: 85%
“…Multiple meta‐analyses from colorectal and non‐colorectal abdominal surgeries all show faster recovery and in many operations also reduced complications. The same trend is true for many non‐abdominal surgeries, such as hip and knee replacement in the elderly, and plastic surgery . Large cohorts also indicate that introduction of ERAS programs may reduce the risks commonly associated with comorbidities such as diabetes .…”
Section: Gains From Implementation Of Erasmentioning
confidence: 85%
“…However, to date, only a few ERPs have been described in the plastic surgery literature (35, 21, 22). Batdorf et al initially described a comprehensive ERP for microsurgical breast reconstruction (3).…”
Section: Discussionmentioning
confidence: 99%
“…They identified the use of multimodal analgesia, lower American Society of Anesthesiologists class, and surgery >6 months after implementation of the pathway as predictors of shorter time to discharge. Bonde et al (5) reported outcomes among patients undergoing unilateral breast reconstruction and found a decrease in mean LOS, from 7.4 to 6.2 days. They continued to improve on their fast-track protocol with the identification of specific factors that prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations